2018
DOI: 10.1111/papr.12674
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerance of Lidocaine 5% Patches in Neuropathic Pain and Pain Related to Vaso‐occlusive Sickle Cell Crises in Children: A Prospective Multicenter Clinical Study

Abstract: Although lidocaine 5% patches decreased the pain's intensity in nearly half of the enrolled patients with an excellent tolerance, the efficacy endpoint was not reached. Further studies should consider a more refined selection of the experimental population to assess the efficacy of lidocaine 5% patches in the pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
1
9
0
1
Order By: Relevance
“…A limited number of studies indicate that 60-100% of children suffering from a peripheral neuropathy benefit from lidocaine patches. [11][12][13]16 Varying success rates are related to differences in neuropathic pain conditions, treatment duration, and definition of outcome. A large study in 115 children reported that 69% benefitted from the use of lidocaine patches (on multiple outcomes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of studies indicate that 60-100% of children suffering from a peripheral neuropathy benefit from lidocaine patches. [11][12][13]16 Varying success rates are related to differences in neuropathic pain conditions, treatment duration, and definition of outcome. A large study in 115 children reported that 69% benefitted from the use of lidocaine patches (on multiple outcomes).…”
Section: Discussionmentioning
confidence: 99%
“…Incidental adverse events are mild to moderate local skin reactions such as erythema, rash, or pruritus. [12][13][14]16 Several studies showed that lidocaine plasma concentrations during patch treatment remained well below systemic therapeutic and toxic ranges in both adults and children. 13,17,18 Thus, lidocaine patches may be a potential safe and noninvasive treatment option in childhood ACNES.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical efficacy, however, could not be assessed in this study, given the small number of patients and lack of randomization to placebo. 106 Moreover, a subgroup analysis of the pain outcomes of SCD patients was not reported.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with HbSS genotype with greater reduction in mean pain scores (P = 0.032) Lidocaine Puri et al 107 2019 Retrospective case series of 4 adolescent patients treated with ketamine and/or lidocaine infusions for VOC. Two of the patients received lidocaine infusions Lidocaine infusion appeared useful in reducing opioid consumption Rousseau et al 106 2018 Prospective, single arm study. 39 pediatric patients (age 6 to 21 years; 23 patients with SCD) treated with 5% lidocaine patches Two-point reduction in pain scores observed in 48.6% of patients after two consecutive days of patch application Nguyen et al 108 2015 Retrospective case series of 11 adult treated with lidocaine infusion for VOC Mean reduction in morphine dose equivalents of 32.2% Abbreviations : RCT, randomized control trial; ED, emergency department; SCD, sickle cell disease.…”
Section: Introductionmentioning
confidence: 99%
“…Por lo tanto, los datos sobre el uso de medicamentos para el dolor neuropático en personas con ECF son limitados. En resumen, se muestran los datos de solo tres ensayos clínicos controlados que investigan los tratamientos centrados en el dolor neuropático en individuos con ECF; un estudio abierto de fase I con un fármaco neuroléptico (trifluoperazina) (53), un ensayo piloto controlado y aleatorizado de seguridad y viabilidad sobre pregabalina sobre 22 pacientes (54) y un estudio de un único brazo de fase II sobre lidocaína transdérmica de 3 días de duración (55). La ketamina (antagonista NMDA), un fármaco que ha demostrado ser eficaz para tratar algunas afecciones de dolor neuropático y cuadros de hiperalgesia, se está perfilando como un posible tratamiento para el dolor de la enfermedad.…”
Section: Dolor Neuropático En La Ecfunclassified